Lâ€™HÃ‰MANGIO-ENDOTHÃ‰LIOME Ã‰PITHÃ‰LIOÃDE (HEE) HÃ‰PATIQUE : ASPECT EN IMAGERIE Dâ€™UN CAS Dâ€™Ã‰VOLUTION FATALE CONFIRMÃ‰ PAR Lâ€™HISTO-IMMUNOCHIMIE ET LA CYTOGÃ‰NÃ‰TIQUE - Tchaou, Mazamaesso; Modruz, Nicoleta; Sonhaye, Lantam; Amdadou, Abdoulatif; Agoda-Koussema, Lama; Nâ€™timon, Bidamin; Hue, StÃ©phane; Rivoal, Edith; Nâ€™dakena, Koffi (European Scientific Journal, ESJ, 2015)
The authors report a case of Hepatic epithelioid hemangioendothelioma in a 40 years old woman admitted for abdominal and pelvic pains in a context of poor general condition. The abdomino- pelvic ultrasound and CT scan had found a diffuse tumor infiltration of the liver. Two liver biopsies, the first ultrasound-guided percutaneous liver biopsy and the second by trans-jugular approch, helped confirm the diagnosis by immunohistochemistry and cytogenetics. Awaiting a liver transplant, she presented a hepatopulmonary synd